Religion, research and the REF-UoA23 education: a thematic investigation - Boeren, Ellen (British Journal of religious education, 2025)
The Research Excellence Framework is the United Kingdom’s means of judging the quality of research produced in its universities and provides an indication of the ‘state of the art’ across subject disciplines. This paper reports on an examination of the submissions made to the Unit of Assessment for Education (UoA23), extracting outputs through relevant keywords. Religious education (RE) is a compulsory curriculum subject in all UK jurisdictions, but there have been ongoing concerns about the quality and range of its provision in schools. Furthermore, religion plays an important focus in educational contexts outside of RE classes given the increased diversity of the population. Through a thematic analysis of relevant submissions to REF 2021 UoA23, this paper reports on the key themes covered by the outputs submitted, to better understand the type of research relating to religion and education that is currently being undertaken in UK universities. The paper raises questions about the future agenda for research on RE and religion in education contexts, and the need to align with any national strategies to address concerns about its future.